A climate change vulnerability index and case study in a Brazilian Coastal City - Zanetti, Vitor Baccarin; Junior, Wilson Cabral de Sousa; De Freitas, Débora M. [UNESP] (MDPI, 2016)
Coastal areas are highly susceptible to the effects of climate change, particularly to sea-level rise and extreme rainfall events, resulting in increased social and environmental vulnerabilities. In this context, the need for predictive planning instruments, especially in densely populated coastal areas, is a critical management priority. A number of indexes has been developed to assess coastal vulnerability. However, coastal vulnerability indexes are yet to simultaneously consider inland (e.g., landslides and flooding) and ocean (sea-level rise and coastal erosion) hazards in conjunction. To help fill this gap, we developed the Socio-Environmental Vulnerability Index for Coastal Areas. The proposed index is a diagnostic tool to assess the socio-environmental vulnerability of coastal regions in the context of climate change. Applied to the city of Santos, a coastal municipality in São Paulo state, Brazil, the index revealed that most of the city are in areas highly vulnerable to sea-level rise and floods related to extreme rainfall events. Findings show that, in fact, approximately 70% of the area of Santos (27.5 km2) consists of high vulnerability areas mostly located close to urban drainage channels, residential, and other built-in areas. Another 0.12% (0.05 km2) were classified as very high vulnerability areas compromising port and industrial infrastructure. These results highlights the susceptibility of the urban insular area of Santos to climatic change hazards. This study might prove relevant to support local decision-makers in preparing adaptation plans and responding to climate-related risks in vulnerable coastal cities.
Keywords: Brazil; Climate change; Coastal areas; Extreme events; Multiple climate hazards